Variabilities of Land Surface Temperature and Frontal Area Index Based on Local Climate Zone - Liguang Li; Ziqi Zhao; Hongbo Wang; Lidu Shen; Ningwei Liu; Bao-Jie He (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2022)
Urban temperature increase brings a challenge to public health, so urban warming has been widely concerned. Within the central area of Shenyang, a 3 × 3 fishnet with nine grids was built to analyze land surface temperature (LST) and frontal area index (FAI) variations based on the local climate zone (LCZ) classification and to explore relationships among them to generate implications for using wind for urban cooling. The results indicate that LST in the 4# grid (central grid) was the highest (35.11 °C) among the nine grids. In general, a higher LST occurred in the grid with a larger building area and vice versa. LCZ-G underwent the largest temperature reduction among the 17 LCZ types. LCZ-2 had the highest LST, while the LCZ-1 had the lowest LST among the three high and intensive building types, except for the LST in the 2# and 4# grids. The FAI in Shenyang decreased from the center to the surroundings. The FAI value was greatest in the 4# grid and the lowest was in the 2# and 8# grids under the prevailing wind of summer and winter. The FAI variations suggested that prevailing SW, SSW, and S winds in summer were difficult to penetrate the central urban area, and the wind cooling effect could not perform. The prevailing NEN and EEN winds in winter could enter the central urban area, enhancing the wind cooling effect, while it was a disadvantage in winter. Overall, there was a significant positive relationship among LST, FAI, and area of LCZ-building.